Right atrial myxoma presenting as a pulmonary embolism in a 32-year-old female. (April 2019) - Pandey, Amitabh C; Carey, John J; Thompson, Jess L
Primary cardiac tumors are typically benign, with myxomas being most common. We present a 32-year-old female with a chief complaint of dyspnea and a constant non-radiating chest pressure along the left sternal border. She was found to have a pulmonary embolism that was ultimately caused by embolization of a right atrial myxoma with remnants of a large, highly mobile mass attached to the right inter-atrial septum prolapsing through the tricuspid valve. The patient underwent a median sternotomy, right atrial mass resection, pulmonary embolectomy, and inter-atrial septum reconstruction using the patient's pericardium. The importance of finding the etiology of initial diagnoses is stressed with long-term outcomes for patients.